Sudi In Vitro Temu Mangga (Curcuma Mangga) sebagai Vasodilator Pembuluh Darah (Jurnal Medika : Karya Ilmiah Kesehatan, 2026)
Background: The prevalence of hypertension in Indonesia and in the world continues to proliferate. Easily accessible new antihypertensive drugs should be explored further. The rhizomes of mango ginger (Curcuma mangga) are abundant in Indonesia, and the rhizome of mango ginger has been known ethnobotanically to treat hypertension, but has yet been scientifically proven.  Purpose: To investigate the vasodilation activity of the rhizome of mango ginger (Curcuma mangga) extract in vitro.  Method: The simplicia of the rhizome of mango ginger was macerated with 99% ethanol. The vasodilation activity was observed by bioassay using a separate organ of Wistar rat aorta whose endothelium was precontracted with phenylephrine. The extract group and the control group (extract solvent) were put into the bioassay chamber with log concentrations of -2, -1.5, -1, -0.5, 0, and 0.5 mg/ml cumulatively. This experiment was replicated 6 times. The aorta vasodilation response is expressed as a percentage of aortic tone and the data are presented in (mean ± SE) %. The statistical test was performed using t-test, and the result is significant if pvalue < 0.05.   Results: The results of the bioassay were as follows: the extract group and control group for log concentration of -2 mg/ml showed aortic vasodilation responses of (5.0 ± 1.9) % and (0.16 ± 0.9) % respectively, with p-value of 0.019; the extract group and control group for log concentration of -1.5 mg/ml showed aortic vasodilation responses of (-7.4 ± 2.5) % and (0.06 ± 0.9) % respectively, with pvalue of 0.01; the extract group and control group for log concentration of -1 mg/ml showed aortic vasodilation responses of (-9.07 ± 2.1) and (0.10 ± 1.1) % respectively, with p-value of 0.02; the extract group and control group for log concentration of -0.5 mg/ml showed aortic vasodilation responses of (-12.75 ± 1.0) % and (-0.39 ± 1.3) % respectively, with p-value < 0.001; the extract group and control group for log concentration of 0 mg/ml showed aortic vasodilation responses of (-16.67 ± 2.1) % and (-1.80 ± 1.2) % respectively, with p-value of 0.002; the extract group and control group for log concentration of 0.5 mg/ml showed aortic vasodilation responses of (-19.015 ± 2.9) % and (-1.71 ± 1.2) % respectively, with p-value < 0.001.   Conclusion: The ethanol extracts of the rhizome of mango ginger (Curcuma mangga) show vasodilation activity on the separate organ of rat aorta with endothelium.   Keywords: Curcuma mangga, Ethanol Extract, Bioassay, Aorta, Vasodilatation.